-7(-5V+1)+5(8+7V)=33

Simple and best practice solution for -7(-5V+1)+5(8+7V)=33 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(-5V+1)+5(8+7V)=33 equation:


Simplifying
-7(-5V + 1) + 5(8 + 7V) = 33

Reorder the terms:
-7(1 + -5V) + 5(8 + 7V) = 33
(1 * -7 + -5V * -7) + 5(8 + 7V) = 33
(-7 + 35V) + 5(8 + 7V) = 33
-7 + 35V + (8 * 5 + 7V * 5) = 33
-7 + 35V + (40 + 35V) = 33

Reorder the terms:
-7 + 40 + 35V + 35V = 33

Combine like terms: -7 + 40 = 33
33 + 35V + 35V = 33

Combine like terms: 35V + 35V = 70V
33 + 70V = 33

Add '-33' to each side of the equation.
33 + -33 + 70V = 33 + -33

Combine like terms: 33 + -33 = 0
0 + 70V = 33 + -33
70V = 33 + -33

Combine like terms: 33 + -33 = 0
70V = 0

Solving
70V = 0

Solving for variable 'V'.

Move all terms containing V to the left, all other terms to the right.

Divide each side by '70'.
V = 0.0

Simplifying
V = 0.0

See similar equations:

| 3s+4=25 | | 2(3x-7)=3x-5 | | X+(-4)=8 | | 2x*x^2-16*4x+3=0 | | 5(6+8B)+8(B-5)=-10 | | m-4m+12=3 | | 5x+10=9x+15 | | [(x-2)-5][(x-2)+3]=0 | | 18+2x=-54 | | 17x+64=13 | | -256=8(7X-6)-4X | | 24x+7*8= | | 5a-2+b-3b+2a= | | 5x-3x+40=50 | | x+109=1+89 | | 3x^2-8x-19=0 | | 70=-17.5n | | 2x=3x-10 | | 12v-3(2+4v)+6= | | 6(1-6X)-4(3X+6)=30 | | -15x+7x+1=3-8 | | 3x^2-22x=0 | | 3x^2-32x-19=0 | | 20x^3-8x^2-5x+2=0 | | 100-x=-39 | | 40-x=-5 | | -4(y-3)+6=2(2y-2)+5y+5 | | 6n^3-24n^2+n-4=0 | | 5+n-p+2n-4= | | 4x-3y=42 | | 4x+3y=42 | | [2x+4]=8 |

Equations solver categories